Appropriateness of bone density measurement in Switzerland: a cross-sectional study - Stefan Zechmann; Nathalie Scherz; Oliver Reich; Beat Brüngger; Oliver Senn; Thomas Rosemann; Stefan Neuner-Jehle (BMC, 2018)
Abstract Background According to the WHO, osteoporosis is one of the most important non- communicable diseases worldwide. Different screening procedures are controversially discussed, especially concerning the concomitant issues of overdiagnosis and harm caused by inappropriate Dual X-ray Absorptiometry (DXA). The aim of this study was to evaluate the frequency and appropriateness of DXA as screening measure in Switzerland considering individual risk factors and to evaluate covariates independently associated with potentially inappropriate DXA screening. Methods Retrospective cross-sectional study using insurance claim data of 2013. Among all patients with DXA screening, women < 65 and men < 70 years without osteoporosis or risk factors for osteoporosis were defined as receiving potentially inappropriate DXA. Statistics included descriptive measures and multivariable regressions to estimate associations of relevant covariates with potentially inappropriate DXA screening. Results Of 1,131,092 patients, 552,973 were eligible. Among those 2637 of 10,000 (26.4%) underwent potentially inappropriate DXA screening. Female sex (Odds ratio 6.47, CI 6.41-6.54) and higher age showed the strongest association with any DXA screening. Female gender (Odds ratio 1.84, CI 1.49-2.26) and an income among the highest 5% (Odds ratio 1.40, CI 1.01-1.98) were significantly positively associated with potentially inappropriate DXA screening, number of chronic conditions (Odds ratio 0.67, CI 0.65-0.70) and living in the central region of Switzerland (Odds ratio 0.67, CI 0.48-0.95) negatively. Conclusion One out of four DXAs for screening purpose is potentially inappropriate. Stakeholders of osteoporosis screening campaigns should focus on providing more detailed information on appropriateness of DXA screening indications (e.g. age thresholds) in order to avoid DXA overuse.